2018
DOI: 10.1002/mnfr.201800519
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐Tocotrienol Attenuates the Hepatic Inflammation and Fibrosis by Suppressing Endoplasmic Reticulum Stress in Mice

Abstract: γT3 supplementation is effective in attenuating NAFLD and fibrosis through a synergistic mechanism of decreased DNL and hepatic ER stress. This work strongly supports the translational potential of γT3 supplementation against NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 54 publications
3
43
1
Order By: Relevance
“…Perhaps, TRF caused more in ammation reduction in visceral WAT and other tissues. Our results are in line with previous reports of the anti-in ammatory effect of TRF but do not con rm some previous studies about the inhibitory effect of gT3 on ER stress (16,29). These studies evaluated the effect of pure gT3 on hepatic ER stress which possibly exerts stronger effects than TRF does.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Perhaps, TRF caused more in ammation reduction in visceral WAT and other tissues. Our results are in line with previous reports of the anti-in ammatory effect of TRF but do not con rm some previous studies about the inhibitory effect of gT3 on ER stress (16,29). These studies evaluated the effect of pure gT3 on hepatic ER stress which possibly exerts stronger effects than TRF does.…”
Section: Discussionsupporting
confidence: 74%
“…In this regard, Gregor et al showed that weight loss reduced ER stress and GRP78 in obesity (9). Moreover, a growing body of evidence has focused on functional foods with anti-in ammatory properties (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, Gregor et al have shown that weight loss reduce ER stress and GRP78 as its marker in obesity (9). Moreover, a growing body of evidence has focused on functional foods with anti-in ammatory properties (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Alphatocopherol is the main form in supplements which has been widely studied. Accumulating evidence suggests that γ-tocotrienol has potential cardiovascular and metabolic health-promoting properties [12], while the biological efficiencies of other isoforms are not established.…”
mentioning
confidence: 99%